Dietary supplements health or hype? - De Robbio, Michael; Jackson, David; Video Education Australasia (Australia : VEA, 2011)
'Take a walk down the aisle of any supermarket or chemist these days and you are bound to be confronted by shelves full of nutrient supplements, ranging from vitamin A to zinc. But are they worth the price you pay for them? This information-packed program takes a balanced look at the essential nutrients needed by the body, the type of person who is most likely to take dietary supplements, and what differences, both good and bad, they can make to our everyday life. This program is a fresh look at a modern multi-billion dollar industry, including the rules of product labeling, and the cunning marketing that leverages off well-known sporting celebrities.'--Container.
Director of photography, Daniel Inglese.
DVD format.
Keywords: Dietary supplements; Vitamins